Student-Based Entrepreneurship Incubation Program for Student Startup Digital Business Development in Efforts to Optimize Sustainable Student Business - Harumy, THF.; Br. Ginting, Dewi Sartika; Manik, F.Y.; Nuzuliati (Talenta Publisher, 2024)
The student digital startup business development incubation program is one of the initiatives implemented to support the development of innovative and sustainable student businesses. This program aims to help students realize their competitive and sustainable business potential. Analysis of the entrepreneurial situation at the University of North Sumatra is currently in the process of development, marked by a large number of new young entrepreneurs from various entrepreneurial programs both internal to the university and outside the university, such as the Young Entrepreneurs program (PMW), Student Creativity Program (PKM), it known that in 2022 there will be 12 PKM funding for the entrepreneurship scheme, apart from that there were also three program winning entrepreneurs (P2MW). The problem is that there are limitations in opening up networking opportunities and market access for students just starting a business. There is a need for education from campuses and assistance regarding good business financial management, and there is still a need to improve sustainable entrepreneurship programs for students. There is a lack of qualified mentors or other resources and support. So, every startup from campus that has just started a business immediately loses enthusiasm and motivation because there is no continuous assistance. The method used to resolve this problem is assistance to improve student startup skills in providing competent human resources, financial assistance, and financial management literacy for student startups, providing facilities in the form of booths and business facilities, training and guidance to improve business management skills, and marketing. This program's online and offline results are characterized by opening up valuable opportunities for students to develop digital business ideas and promote sustainable business principles, allowing student businesses to contribute to sustainable growth.